Selection of the best air purifier system to urban houses using AHP - Delgado, Alexi (2017)
Pollutants inside at houses are smoking, gas combustion, use of solvents, household cleaning chemicals, emissions from building materials, and contamination of the exterior aggravates the inside of the house. In this article, we conducted a study to select the best air purifier equipment for an urban house. The selection was carried out by applying the analytic hierarchy process (AHP) methodology. In this study, three alternatives were proposed for the evaluation of the air purifier equipment: Bap1700, Bap600 and Bap706; which were ranked according to the criteria: scope, characteristics, and model. To carry out the selection using AHP, a panel of four experts were selected for this study. In this paper, we determined that the best air purifier equipment was the A1 alternative: Air Purifier Bap1700.